Correction to: Tumour suppressor EP300, a modulator of paclitaxel resistance and stemness, is downregulated in metaplastic breast cancer - Asaduzzaman,M; Constantinou,S; Min,H; Gallon,J; Lin,M-L; Singh,P; Raguz,S; Ali,S; Shousha,S; Charles,Coombes R; Lam,EW-F; Hu,Y; et al. (Breast Cancer Research and Treatment, 2018)
In the original publication, Fig. 1 depicting the blot for EP300 in CAL51 cells (Fig. 1c) was unintentionally duplicated with that from MDA-MB-231 cells (Fig. 1d). The new figure given in this erratum depicts the correct EP300 blot in Fig. 1c.